PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN LKPD TERHADAP HASIL BELAJAR IPAS DI SDN 92 SINGKAWANG - Mukhlisin; Murdani, Eka; Setyowati, Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: (1). To find out whether there are differences in science learning outcomes between students using the problem based learning (PBL) model assisted by LKPD and conventional learning. (2). To find out how much influence the problem based learning (PBL) model assisted by LKPD has on science learning outcomes at Sdn 92 Singkawang. The experimental research design in this research uses the form of Nonequivalent Control Group Design. The population in this study was class IVA and class IVB at Sdn 92 Singkawang. Based on the results of the research and discussion in the previous chapter, it can be concluded that: (1). There are differences in science learning outcomes between students using the problem based learning (PBL) model assisted by LKPD and conventional learning. This is proven by data analysis carried out using parametric statistical tests, namely the T test, t hitung > t tabel on the post-test results. (2). The application of the problem based learning (PBL) model assisted by LKPD on science learning outcomes at Sdn 92 Singkawang has a moderate effect. This is proven by the results of calculating student data using the Effect Size formula, resulting in an Effect Size (Es) value of 0.7, which is in the medium criteria. (3). Problem based learning (PBL) learning has experienced a moderate increase towards students' cognitive domain learning outcomes in class IV Energy Resources material at Sdn 92 Sigkawang.